Biomechanical characterization of three iliac screw fixation techniques: A finite element study. (June 2018) - Sohn, Seil; Park, Tae Hyun; Chung, Chun Kee; Kim, Yongjung Jay; Jang, Jong Wuk; Han, In-bo; Lee, Sung Jae
Highlights: We previously reported a modified iliac screw fixation technique which addressed the limitations of the classic iliac screw fixation and the S2 alar iliac screw (S2AI) fixation techniques. The PVMS values of the 3 different iliac screw fixation techniques were lower than the fatigue strength levels under physiological loadings. PVMS of iliac screws was observed in the screw shaft for S2AI, in the screw neck for the modified iliac screw technique, and in the offset connectors of the classic iliac screw technique. The interaction between the screw head and the neck was compressed in modified iliac screw fixation technique. On the other hand, distraction force was observed in the S2AI technique. Abstract: We aim to characterize the biomechanical properties of a modified iliac screw fixation method compared with the classic iliac screw fixation and the S2 alar iliac screw (S2AI) fixation using a FEM. A three-dimensional, non-linear FEM of lumbosacral spine and pelvis (L1-pelvis) was modified to simulate 3 different iliac screw fixations based on posterior screw fusion. The peak von Mises stress (PVMS) values of the iliac screws in the 3 different iliac screw fixations were recorded in during flexion/extension/axial rotation/lateral bending. The interaction stress which arose between the screw head and the shaft of iliac screws, was also measured for each case. The PVMS values of the 3 different iliac screw fixation techniques were lower than the fatigue strength levels under physiological loadings. PVMS of iliac screws was observed in the screw shaft for S2AI, in the screw neck for the modified iliac screw technique, and in the offset connectors of the classic iliac screw technique. The interaction between the screw head and the neck was compressed in modified iliac screw fixation technique. On the other hand, distraction force was observed in the S2AI technique between the screw head and the screw shaft. This FEM study supports our previous clinical results, which found that the modified iliac screw fixation technique can be an effective alternative sacropelvic fixation technique comparable to the classic iliac screw and the S2AI technique.